You are on page 1of 2

1.

- (p→q)˄( q
̴ ↔p)

p q ̴q p→q ̴q↔p (p→q)˄( q


̴ ↔p)
V V F V F F
V F V F V F
F V F V V V
F F V V F F

2.- (p˄ q
̴ ) ѵ (̴ p
̴ ↔q)

p q ̴p ̴q p˄ q
̴ ( p
̴ ↔q) ̴( p
̴ ↔q) (p˄ q
̴ )ѵ (̴ p
̴ ↔q)
V V F F F F V V
V F F V V V F V
F V V F F V F F
F F V V F F V V

3.- (p˄q)↔( p
̴ ѵq)

p q ̴p p˄q ( p
̴ ѵq) (p˄q)↔( p
̴ ѵq)
V V F V V V
V F F F F V
F V V F V F
F F V F V F

4.- p → (̴ q∆ p
̴ )

p q ̴p q∆ p
̴ ̴(q∆ p
̴ ) p → (̴ q∆ p
̴ )
V V F V F F
V F F F V V
F V V F V V
F F V V F V

5.- p
̴ ∆ (p→ q
̴ )
p q ̴p q
̴ p→ q
̴ ̴p Δ(p→ q
̴ )
V V F F F F
V F F V V V
F V V F V F
F F V V V F

6.- (p˄q)↔ (̴ p→ q
̴ )

p q q
̴ p˄q p→ q
̴ ̴(p→ q
̴ ) (p˄q)↔ (̴ p→
q
̴ )
V V F V F V V
V F V F V F V
F V F F V F V
F F V F V F V